Association of physiological levels for Glutathione with some clinical symptoms in COVID-19 patients - Al-Mamoori, Noor Hadi obaid; Shuwaikh, Afaf K.; Alkharsan, Noor H.; Ghanim, Zainab; Al-Musawi, Hawraa Sabah; ketran, Rana mozher; Muttaleb, Wurood Hamzah; Jumaah , Hind Mahmood (Iraqi Journal of Science, 2025)
Maintaining optimal glutathione (GSH) levels is essential for preserving cellular integrity, preventing oxidative damage, and mitigating inflammation, thereby safeguarding against a wide range of diseases. ‏‏The present study was suggested to evaluate GSH level in COVID-19 cases and analysis some associations with disease biomarkers and characteristics, including D-dimer, ferritin, age, BMI, sex, Ct-scan, duration, and severity of infection. The results found that GSH was decreased in infection cases than the control group in a significant change (p= 0.011). D-dimer and ferritin showed significant elevation in cases with significant differences (p=0.003, p=0.000). The Ct-scan in the cases group was 33.18%, and infection duration (11.08) days, non-significant (non-sig) changes between both groups in BMI (p=0.346). GHS was higher in males than females in both groups, with non-significant differences. In the cases group, D-dimer was significantly higher in males, while in control, non-sig differences were observed according to sex, while ferritin levels and the clinical parameters displayed non-sig changes. GSH level showed elevation in simple and sever infection level in non-sig changes (p=0.291), D-dimer increased with severity of infection significantly (p=0.008), and ferritin also increased with infection severity significantly (p=0.000). The correlation analysis between GSH level and D-dimer revealed a significant inverse correlation (p= 0.037*) in COVID-19 cases. In contrast, the correlation of GSH with the remainder of the study variables showed a non-significant correlation in both groups (cases and control). Conclusion: The present finding concluded that GSH has a significant depletion in many COVID-19 cases and a negative correlation with D-dimer, suggesting a potential link between GSH levels and disease severity.